Evaluation of the Implementation of RSPO Standardisation (Roundtable for Sustainable Palm Oil) on Oil Palm Smallholders for Sustainability in KUD Teratai Biru and Kud Permai Jaya - Yuli Sari Yeni; Budi Santosa (Budapest International Research and Critics University, 2023)
This study aims to analyse the implementation of RSPO standardisation on oil palm smallholders as members of cooperatives KUD Teratai Biru and KUD Permai jaya. To analyse the challenges faced by cooperatives related to the implementation of RSPO standardisation. To analyse the strategies applied by the cooperatives in facing the challenges of effective and efficient implementation of RSPO standardisation so as to increase the productivity and welfare of oil palm smallholders. This study used a qualitative approach to analyse the role of village unit cooperatives in RSPO standardisation to oil palm smallholders as cooperative members as well as the issues and strategies applied with the aim of increasing productivity and improving welfare. The subjects of this study were KUD Teratai Biru and KUD Permai jaya. The survey respondents were cooperative management and cooperative members, namely farmers. Primary data was obtained from interviews and questionnaires distributed to members and administrators who responded to the survey. Based on the analysis of the impact of the implementation of the Roundtable for Sustainable Palm Oil (RSPO) Standardisation on oil palm farmers, the impact of standardisation on cooperative members can improve the management of oil palm plantations and also have an impact on increasing the welfare of oil palm farmers and with the existence of the program can overcome the problems that have been a problem of cooperative members and oil palm farmers. To improve innovation performance, cooperatives must be more proactive in responding to various issues related to changes in the cooperative environment both internally and externally. These changes must be responded wisely through research and development activities so that the co-operative can maintain its existence in the future.